Tuturan Komburongo in the Context of Oral Narrative and Belief of the Tobilung Ethnic Group of Sabah: (Tuturan Komburongo dalam Konteks Cerita Lisan dan Kepercayaan Etnik Tobilung di Sabah) (Malay Literature, 2021)
The oral narratives that revolve around Komburongo are known as tuturan Komburongo among the Tobilung ethnic group in Sabah. The purpose of this article is to analyze the elements of belief contained in these stories. All the tuturan Komburungo that are analyzed in this article are obtained from fieldwork interviews with informants from the Tobilung ethnic group in the district of Kota Belud, Sabah. The important issues dealt with in this article are concerned with the Tobilung ethnic group's belief in the supernatural powers of Komburongo, as told in their oral literature. The result of the analysis by way of interpretation in this study finds that the tuturan Komburungo are divided into myth or legend in the context of folklore. On the question of its origin, Komburongo is believed to have been created by Tinamaru, the Creator of the Tobilung. The traditional Tobilung ethnic group are found to be highly dependent on Komburongo as the good spirit that provides guidance and possesses magical powers that help to solve various life crises for generations. This study is considered significant because it highlights many aspects of the belief of the Tobilung ethnic group passed down from generation to generation based on tuturan Komburungo.